Frequent procedural errors and structural complications on endodontical treated teeth - Sanziana Adina Scarlatescu; Irina Gheorghiu; George Nicola; Andrei O. Al Aloul; Paula Perlea (Amaltea Medical Publishing House, 2021)
The objectives of root canal treatment are to prevent the apical parodontitis, to heal the acute or cronic apical periodontits and to maintain the results, keeping the teeth on the arch in a functional stage. Thus, accuratelly elimination of soft and hard tissues (cleaning and shaping of the root canal system), disinfection and complete, homogeneous and tridimensional filling of the root canal system are very important to successful endodontic treatment. Modern concepts in endodontic treatment rely on technological progress and therefore many cases are successfully fulfilled, but the practitioner may be put in front of procedural errors both during and after endodontic treatment. Apical blockage, ledging, zipping, stripping, perforations in the floor of the pulp canal chamber or root canals perforations are the most common errors, but in many clinical situations they can be prevented and even surpassed once happened.